Lipopolysaccharides from Campylobacter jejuni associated with Guillain-Barré syndrome patients mimic human gangliosides in structure. - Aspinall, G O (1994)
Lipopolysaccharides extracted from Campylobacter jejuni serostrains (serotype reference strains) for serotypes O:4 and O:19 were found to have core oligosaccharides with terminal structures resembling human gangliosides GM1 and GD1a. High-molecular-weight molecules that reflected the presence of O chains were shown in immunoblots to be immunologically specific for each serostrain. The O:19 antiserum also reacted strongly with core oligosaccharides of two isolates from patients with Guillain-Barré syndrome (GBS), but the banding patterns and molecular structures were different from those of the O:19 serostrain. A neuraminobiose disaccharide unit is attached to the terminal Gal residue in one isolate, and the other isolate lacked terminal N-acetyl glucosamine and galactose with attached sialic acid so that the sialic acid residues were present in a neuraminobiose unit linked to the only remaining galactose. Analysis of the high-M(r) lipopolysaccharides of the O:19 serostrain and the two isolates from GBS patients revealed the presence of a hyaluronic acid-like polymer with disaccharide-repeating units consisting of beta-D-glucuronic acid amidated with 2-amino-2-deoxyglycerol and N-acetyl glucosamine. The results confirm a potential role for the core oligosaccharides in the etiology of GBS but also suggest that the O-chain polysaccharide may be a contributing factor.